Myopathy as a cause of fatigue in long‐term post‐COVID‐19 symptoms: Evidence of skeletal muscle histopathology. (23rd June 2022) - Hejbøl, Eva K.; Harbo, Thomas; Agergaard, Jane; Madsen, Line B.; Pedersen, Thomas H.; Østergaard, Lars J.; Andersen, Henning; Schrøder, Henrik D.; Tankisi, Hatice
Abstract: Background and purpose: Among post‐COVID‐19 symptoms, fatigue is reported as one of the most common, even after mild acute infection, and as the cause of fatigue, myopathy diagnosed by electromyography has been proposed in previous reports. This study aimed to explore the histopathological changes in patients with post‐COVID‐19 fatigue. Methods: Sixteen patients (mean age = 46 years) with post‐COVID‐19 complaints of fatigue, myalgia, or weakness persisting for up to 14 months were included. In all patients, quantitative electromyography and muscle biopsies analyzed with light and electron microscopy were taken. Results: Muscle weakness was present in 50% and myopathic electromyography in 75%, and in all patients there were histological changes. Muscle fiber atrophy was found in 38%, and 56% showed indications of fiber regeneration. Mitochondrial changes, comprising loss of cytochrome c oxidase activity, subsarcollemmal accumulation, and/or abnormal cristae, were present in 62%. Inflammation was found in 62%, seen as T lymphocytes and/or muscle fiber human leukocyte antigen ABC expression. In 75%, capillaries were affected, involving basal lamina and cells. In two patients, uncommon amounts of basal lamina were found, not only surrounding muscle fibers but also around nerves and capillaries. Conclusions: The wide variety of histological changes in this study suggests that skeletal muscles may be a major target of SARS‐CoV‐2, causing muscular post‐COVID‐19 symptoms. The mitochondrial changes, inflammation, and capillary injury in muscle biopsies can cause fatigue in part due to reduced energy supply. Because most patients had mild–moderate acute affection, the new variants that might cause less severe acute disease could still have the ability to cause long‐term myopathy. Abstract : This study analyzes muscle biopsies from 16 patients experiencing persistent muscle fatigue 5–14 months after COVID‐19 infection. All patients displayed some histological changes. The changes included signs of muscle fiber damage and regeneration, mitochondrial changes, signs of inflammatory myopathy, capillary pathology, and nerve involvement. There was no correlation of the histopathological findings with the severity of the acute infection, and none of our patients had been referred to intensive care. The study confirms our previous electromyographic observation of myopathy.